Indian Interest in the Arctic in the Context of China’s Arctic Policy - Nikolay A. Nikolaev (Проблемы постсоветского пространства)
The study examines the general and excellent in the Arctic policy of India and China and the likelihood of rivalry between the two Asian powers in the allocation of resources to the Arctic. Also, Indian and Chinese research trends on Arctic topics were considered.Since the middle of XX century. India and China act as long-standing rivals. Periodically, military clashes broke out between the two sides on a common border. Despite the fact that the key territorial issues on the common border between India and China are resolved military provocations from both sides do not stop. The latest incident was the transfer of Indian troops to the Chinese border zone in the province of Sikkim. Both powers of Asia are major consumers of energy resources, they are more or less interested in the situation on the global energy market.In the Arctic there are colossal reserves of various resources. Certain difficulties and limitations with access to resources and their equitable distribution can force these countries to compete with each other. However, the lack of a specific position on Arctic issues or the formulated regional strategy for India and China creates a lot of doubt about their true intentions. The study of research trends, the activity of Indian and Chinese business structures, as well as the arctic activities of India and China, gives approximate answers to this question.The potentials of India and China are very different in the Arctic. China’s strengths are active participation in international scientific research, the availability of a qualified ice-class crew, active investment in energy and infrastructure projects in the Arctic countries, and fairly stable trade relations with most Arctic countries. The weak side of China is its negative image. Residents of many Arctic countries are very wary of the «rise of China» and its growing interest in the Arctic.Strengths of India are a positive image and a representative diaspora in the Arctic countries, especially in the US and Canada. In the future this will allow Delhi to successfully promote initiatives in the Arctic. The weak side of India can be considered the absence of a ship «icebreaker class», the weak investment activity of Indian business structures and poor knowledge of Arctic problems from the point of view of Indian issues.